2017
DOI: 10.1002/jcp.26228
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐145‐5p inhibits proliferation and inflammatory responses of RMC through regulating AKT/GSK pathway by targeting CXCL16

Abstract: The main pathological characteristics of chronic glomerulonephritis (CGN) are diffuse mesangial cells proliferation and inflammatory responses. Our previous studies have confirmed that miR-145-5p was abnormally elevated in CGN rats, but its mechanism remains unclear. Therefore, this study aimed to elucidate the mechanism of miR-145-5p in regulation of renal mesangial cells proliferation and inflammatory responses. In vivo study, the cationic bovine serum albumin (C-BSA)-induced CGN rat model was established, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 40 publications
(51 reference statements)
1
29
0
Order By: Relevance
“…The importance of miR-145 in the immune system has been sporadically studied. 28 We demonstrated that miR-145 overexpression had no impact on the release of IL-1β, IL-6, IL-8, and TNF-α in the LPS-untreated MH7A cells, but it could reduce the release of these pro-inflammatory cytokines in LPS-stimulated MH7A cells. 28 Moreover, miR-145 was reported to exert anti-inflammatory functions via inhibiting the expression of pro-inflammatory cytokines IL-1α, IL-2, IL-6, and TNF-α.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The importance of miR-145 in the immune system has been sporadically studied. 28 We demonstrated that miR-145 overexpression had no impact on the release of IL-1β, IL-6, IL-8, and TNF-α in the LPS-untreated MH7A cells, but it could reduce the release of these pro-inflammatory cytokines in LPS-stimulated MH7A cells. 28 Moreover, miR-145 was reported to exert anti-inflammatory functions via inhibiting the expression of pro-inflammatory cytokines IL-1α, IL-2, IL-6, and TNF-α.…”
Section: Discussionmentioning
confidence: 72%
“…28 Moreover, miR-145 was reported to exert anti-inflammatory functions via inhibiting the expression of pro-inflammatory cytokines IL-1α, IL-2, IL-6, and TNF-α. 28 We demonstrated that miR-145 overexpression had no impact on the release of IL-1β, IL-6, IL-8, and TNF-α in the LPS-untreated MH7A cells, but it could reduce the release of these pro-inflammatory cytokines in LPS-stimulated MH7A cells. Collectively, our finding suggested that miR-145 could protect MH7A cells against LPS-induced inflammatory injury.…”
Section: Discussionmentioning
confidence: 99%
“…It is now widely accepted that the IL‐23–IL‐17A axis plays a central role in the development of psoriasis. Several studies have shown that miR‐145‐5p inhibits cell proliferation and immune responses . We identified a protective association of miR‐145‐5p with psoriasis, and downregulation of miR‐145‐5p contributes to keratinocyte proliferation and skin inflammation.…”
Section: Discussionmentioning
confidence: 80%
“…In this study we performed a miRNA microarray and found that miR‐145‐5p was downregulated in psoriasis. Recent studies suggest that miR‐145‐5p suppresses inflammation in several inflammatory diseases . The potential regulatory mechanisms of miR‐145‐5p have been investigated, and miR‐145‐5p was shown to regulate inflammatory diseases by modulating various signalling pathways, such as the Akt–glycogen synthase kinase pathway, the mitogen‐activated protein kinase signalling pathway and the mammalian target of rapamycin–nuclear factor (NF)‐κB signalling pathway …”
mentioning
confidence: 99%
“…However, Si-circ_19698-1 also led to the obvious down-regulation of Tnfrsf21 (the linear host gene for circ_19698). TNFRSF21, also called death receptor 6 (DR6), belongs to the tumor necrosis factor receptor super-family, and is often reported to induce cell apoptosis [54,55], or inhibit the proliferation and invasion of head and neck squamous cell carcinoma cells [56]. Therefore, TNFRSF21 likely exhibited a reduced inhibitory effect on the proliferation of BRL3A cells and antagonized the inhibitory role of Si-circ_19698-1 during BRL3A proliferation, once its expression was decreased by Si-circ_19698-1.…”
Section: Discussionmentioning
confidence: 99%